Complications related to unwitnessed magnet ingestion in paediatrics: case report - Suresh Kumar; Ghani, Amarah (Journal of the Pakistan Medical Association, 2023)
Foreign body ingestion is one of the most common problems among children. There is a great tendency among children between the age of six months to six years to place objects, such as coins, fish bone, pins, button batteries, magnets and other household items, in their mouth and often swallow them. Magnet ingestion is not uncommon. Hazardous effects can occur owing to the fact that these are usually unwitnessed leading to disparity in history and delayed presentation. Nowadays these magnets are made of Neodymium which is a strong element and can be moulded into various shapes and sizes, making them more attractive to children. Single magnet ingestion may pass without complication, but multiple ingested magnets pose risk of severe complications such as obstruction, inter bowel fistulae, and perforation often requiring urgent intervention3. ---Continue